Visual Literacy in Teacher Training: Systematic Review According to Prisma 2020 Guidelines - Mendoza Ureta, Raquel Stefania (2023)
Visual literacy is a set of skills that enable an individual to employ visual resources effectively. These are essential to face today society’s challenges, where image predominates in the exchange of information. The objective of this work was to determine how visual literacy is related to teacher training, and to specify what proposals have been developed. To this end, a systematic review was carried out, considering the guidelines of PRISMA 2020 declaration. In this process, a search string was used in five databases, and eligibility criteria were applied, to assess the relevance of the articles; those relevant were selected and included. The results show that when teachers are trained in visual literacy, they acquire visual skills for daily life, and they promote changes within their educational practices with the intention of improving the quality of teaching. Most of the proposals that were found promote ways to visually train teachers using the arts field.